PENGEMBANGAN MEDIA LACI HITUNG PADA MATERI PERKALIAN SISWA KELAS II SEKOLAH DASAR - Handayani, Fitri; Saidah, Karimatus (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
The purpose of this research and development is to describe the product definition of Laci Hitung media in elementary school grade II multiplication material; 2) designing a Laci Hitung media product design on the multiplication material developed in grade II of Elementary School; 3) produce Laci Hitung media products on the multiplication material developed in the learning of grade II elementary school students as well as the advantages and disadvantages of products that have been developed. Development research models use 4D models that are modified to 3D (Define, design, development,) This model was chosen because it is adaptive, systematic and in accordance with this development research. The development results are in the form of counting drawer media consisting of drawers that are given numbers and funnels to put marbles into the drawer. The advantages of this media include making it easier for students to learn multiplication, it can be used for all number operations and makes it easier for teachers to convey material about multiplication. While the disadvantage is that it cannot be used for hundreds and thousands number operations.